FINANCE IS AN ECONOMIC CONCEPT - Baltabayeva, Maloxat Ortiqaliyevna (GOLDEN BRAIN, 2024)
This article reflects on Accounting Science and accounting. A specialist who has studied accounting understands finance and is able to carry out finance, enterprise or public finance, there will be a cadre that manages to calculate profit in advance. Therefore, it is not for nothing that we call the name of our article business language.